Pengaruh Inflasi Terhadap Tingkat Pengangguran Terbuka Di Provinsi Jawa Tengah - Nuraeni, Annisa; Alfarisi, Muhammad Salman; Sohib, Muhammad; Hidayat, Raden Ahmad; Nazla, Zavita; Desmawan, Deris (Universitas Labuhanbatu, 2024)
Our research aims to determine whether inflation has an influence on open unemployment in Central Java province. The Data we use comes from BPS Central Java. Secondary Data in the period 2013-2018 is the data we use. When analyzing data using simple regression testing, certainty test (R2) and partial testing (t-test) is a hypothesis test with SPSS 24. The results of our research show that the inflation rate in Central Java province has the power to influence the unemployment rate in Central Java province.